Role of Ultrasound Imaging in Children with Dengue Fever: A Retrospective Study - Sean Martin, Juliet Anitha; Annadurai, Karthikeyan (International Journal of Integrated Health Sciences, 2024)
Objective: To study ultrasound findings of children with dengue and analyze the possible correlation between ultrasound findings  and severity of dengue in children.Methods: This retrospective study, which was conducted over one year, analyzed 50 pediatric dengue patients. Ultrasound findings such as gallbladder wall edema, pleural effusion and ascites were assessed. Cases were categorized into dengue without warning signs, dengue with warning signs, and severe dengue according to the World Health Organization's classification of dengue. Correlation between ultrasound abnormalities,  severity of dengue, and  thrombocytopenia were analyses. A p-value of less than 0.05 was taken as statistically significant.Results: Of 50 pediatric patients diagnosed with dengue participated in this study, 72% were boys, and 28% were girls with a male-to-female ratio of 1:0.38. Fever was the most frequent symptom (100%), followed by nausea/vomiting (84%) and body ache/myalgia (78%). Ultrasound findings revealed that gallbladder wall edema (48%), pleural effusion (44%), and ascites (50%) were significantly associated with severe dengue and dengue with warning signs (p<0.001). Thrombocytopenia was documented in 58% of cases and correlated significantly with ultrasound abnormalities such as gallbladder wall edema, ascites, and pleural effusion (p=0.0017).Conclusion: Ultrasound findings, such as gallbladder wall edema, pleural effusion and ascites, are significantly associated with severe dengue and dengue with warning signs. These features aid in early identification of high-risk patients.